Hubungan Antara Pengetahuan Dan Persepsi Ibu Tentang Gizi Seimbang Dengan Pemilihan Makanan Jajanan Pada Anak Balita Di Wilayah Puskesmas Gilingan Surakarta - VIENSKA RANIE, ATA, Dr.Mutalazimah,SKM.,MKes, Rustiningsih, SKM., M.Kes (2015)
DEPARTMENT OF NUTRITION SCIENCE FACULTY OF HEALTH SCIENCE Introduction: Snack is the food and beverages served and sold by street vendors, food shops, supermarkets in the streets and crowded places. Snack selection behavior is influenced by internal and external factors. Internal factors influencing snack selection, namely knowledge and perception of the mother. Knowledge of nutrition is very influential in the selection of snack for children under five is the cornerstone of behavior change. Objective: To determine the relationship of mother's knowledge and perceptions about balanced nutrition by snack selection among children under five in the Gilingan primary service center. Methods: This study using observational method with the cross sectional design with the total sample of 46 respondents. The research instruments in the form of a questionnaire knowledge , perception and snack selection. Test analysis techniques is the Pearson Product Moment. Results: Most of mother's knowledge about balanced nutrition is moderate (47,8%). Perception mothers about balanced nutrition classified as good (54,3 %). Snack selection in children under five mostly classified as good (58.7%) Conclusion: There was no relationship between mother's knowledge about balanced nutrition with snack selection in children under five (p = 0.466) and there was no relationship between the perception of mothers about balanced nutrition with the snack selection in children under five (p = 0.315) in the region of Surakarta Gilingan primary service center. Keywords : Knowledge, Perception, Snack Selection Bibliography : 2002-2014